Left main coronary artery atresia in a 2-year-old toddler with de novo heart failure: Case report and review of the literature - Asl Fallah, Sahar; Mahdavi, Mohammad; Rezaei-Kalantari, Kiara; Qanadli, Salah D.; Mirsadraee, Saeed (Frontiers in Cardiovascular Medicine, 2022)
Congenital coronary anomalies are among the rare disorders of the otherwise normal heart. A 2-year-old child evaluated for denovo heart failure after a flu-like event two months before suspicious for post Covid-19 dilated cardiomyopathy. Cardiac Magnetic Resonance (CMR), displayed the basal to mid subendocardial to transmural scar suggestive for an ischemic etiology. Further assessment with CT and invasive angiography confirmed the very uncommon left main artery atresia (LMCAA) as the culprit for patient heart failure. This is not only the first reported LMCAA case undergone CMR study but also initially suspected with characteristic CMR findings.